Upaya Peningkatan Pengetahuan Gangguan Aktivitas Sehari Hari pada Lansia di Puskesmas Kendalsari Kota Malang - Kurniawati Putri Al Saudi; Sri Sunaringsih Ika Wardojo; Bonita Suharto (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
As cities in Indonesia continue to develop, there will inevitably be ignorance of the elderly's knowledge of their own health. For example, elderly people with working backgrounds are generally at risk of lower back pain, pinched nerves, complaining of various muscle tension problems and so on which can disrupt their daily activities. This problem is caused by incorrect positioning while working, such as frequently pushing, lifting, bending, sitting or standing for long periods of time and unergonomic body posture while working. Physiotherapy outreach activities related to increasing knowledge of daily activity disorders, efforts to educate the elderly regarding activity disorders, especially about definitions, signs of symptoms, causes, prevention, and daily activity activity therapy independently after work to reduce the symptoms suffered. This outreach activity uses leaflets as media, containing educational material for the elderly, then education and training depending on the location of the disorders the elderly complain of. The counseling activities at the Mobile Health Center Posyandu which are held every day by the Kendalsari Community Health Center, Malang City, went smoothly, the response was good, full of enthusiasm. The results obtained show the results of the pretest so that there is increased knowledge among workers which shows that workers have knowledge and insight regarding prevention and independent treatment after work. The results obtained showed that most of them were mild complaints, so that the majority of complaints involving disruption of daily activities were experienced by women, 68% of which were indicated by questionnaires for 25 elderly people at the Kendalsari Community Health Center and Posyandu for the Elderly in Malang City.